A grafting study on partially dehydrochlorinated poly(vinyl chloride) by atom transfer radical polymerization - Coskun, Mehmet; Barim, Ganize; Demirelli, Kadir (Taylor & Francis Inc, 2007)
HCl elimination in low ratio was first carried out from poly(vinyl chloride) to increase allylic chlorines. Partially dehydrochlorinated poly(vinyl chloride), having a macroinitiator effect, was grafted with tert-butyl methacrylate via atom transfer radical polymerization in the presence of CuBr/2',2'-bipyridine at 64 degrees C in tetrahydrofuran. Original poly(vinyl chloride) was also grafted with tert-butyl methacrylate under the same conditions to compare with that of partially dehydrochlorinated poly(vinyl chloride). The graft copolymers were characterized by elemental analysis, FTIR, H-1 and C-13-NMR, differential scanning calorimetry, and gel permeation chromatography (GPC). Thermal stabilities of the graft copolymers were investigated by thermogravimetric analysis as compared with those of the macroinitiators.
Keywords: PVC; graft copolymer; atom transfer radical polymerization; thermal properties